Partners in crime? Post-release recidivism among solo and co-offenders in Norway. Issue 2 (3rd July 2019) - Andersen, Synøve Nygaard
ABSTRACT: Co-offending may increase offenders' criminal capital in ways that impact their subsequent offending behaviour, and while highly theorized, the relationship between co-offending and reoffending has received less attention in empirical research. This study relies on Norwegian registry data to explore patterns of registered co- and solo offending before and after offenders' first release from prison, by assessing differences in total, solo and co-reoffending between (1) co-offenders and solo offenders and (2) co-offenders embedded in different co-offending networks. The sample is based on 10 complete release cohorts, and co-offending networks are constructed from 22 years of administrative police data. Egocentric network analysis is used to obtain measures of degree centrality and tie strength. Results show that recidivism rates are higher among individuals with a co-offending network at release, and there is a consistent, positive relationship between degree centrality and reoffending. There is also a positive correlation between time spent in prison and the likelihood of co-offending after release, but there are no incidents of repeated co-offending (i.e. reoffending with co-offenders acquired before incarceration). The analysis hereby confirms several well-known patterns of co-offending in a new national context and highlights how incarceration can shape the nature and longevity of egocentric co-offending network ties.